2021
DOI: 10.1016/j.scitotenv.2020.142156
|View full text |Cite
|
Sign up to set email alerts
|

Effects of polycyclic aromatic hydrocarbons and abiotic stressors on Fundulus grandis cardiac transcriptomics

Abstract: Salinity and temperature alone are not important drivers of gene expression. • Genes involved in xenobiotic metabolism, cardiac development & function upregulated • Increased cardiomyocyte proliferation and hypertrophy & inhibited contractility • Systemic vasculature heavily impacted under multiple stressors • Complex interactions under multiple stressors do not appear to be additive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 71 publications
(111 reference statements)
0
3
0
Order By: Relevance
“…The pattern of GST levels occurred regardless of the tissue-concentration of PAHs, which possibly indicated that the detoxification activity responded to the compounding of low salinity on PAH burden rather than the increasing PAH accumulation at lower salinities. Such apparent changes in toxicity due to reduced salinity were not observed in a number of studies that varied abiotic factors during the exposure of fish to a water attenuated fraction of weathered oil (Serafin et al, 2019;Simning et al, 2019;Allmon et al, 2021). Additionally, Schrandt et al (2018) found that oil (MC252)-exposed juvenile C. virginica showed a clear interaction between oil exposure and salinity on the survivorship and shell growth.…”
Section: Salinity and Pahsmentioning
confidence: 95%
“…The pattern of GST levels occurred regardless of the tissue-concentration of PAHs, which possibly indicated that the detoxification activity responded to the compounding of low salinity on PAH burden rather than the increasing PAH accumulation at lower salinities. Such apparent changes in toxicity due to reduced salinity were not observed in a number of studies that varied abiotic factors during the exposure of fish to a water attenuated fraction of weathered oil (Serafin et al, 2019;Simning et al, 2019;Allmon et al, 2021). Additionally, Schrandt et al (2018) found that oil (MC252)-exposed juvenile C. virginica showed a clear interaction between oil exposure and salinity on the survivorship and shell growth.…”
Section: Salinity and Pahsmentioning
confidence: 95%
“…An important body of the literature describes the mechanisms that, in aquatic species, sustain cardiac adaptation to environmental challenges, with attention not only to the upper and lower limits of this adaptation, but also to the molecular pathways that are recruited during the exposure to multiple challenges, an event that is becoming more and more frequent in damaged natural environments. A recent example is the cardiac transcriptomic response described in Fundulus grandis developing larvae to four combined stressors (O 2 availability, temperature, salinity, and polycyclic aromatic hydrocarbons) [ 7 ]. It was found that each single stress, administered alone, affects the heart in terms of beat-to-beat hemodynamic and development.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, stress combination potentiates the effects on the heart, either positively or negatively, by affecting canonical pathways involved in heart contractility, vasomotility, and cardiomyocyte proliferation. These pathways include the cardiac nitrergic system [ 7 ]. As demonstrated by many papers, in the heart, this system is at the crossroads of many stress-sensitive circuits [ 8 , 9 , 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%